1978
DOI: 10.1007/bf02533845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of essential fatty acid deficiency on prostaglandin synthesis and fatty acid composition in rat renal medulla

Abstract: Studies are reported on the capacity of isolated rat renal papilla (inner medulla) to synthesize and release prostaglandin (PG) E from endogenous and exogenous precursor(s) during development of an essential fatty acid (EFA) deficiency in the rat. Weanling (21-day-old) male Sprague-Dawley rats were fed a fat-free diet supplemented with either 5% hydrogenated coconut oil (HCO) or 5% safflower oil (SO). At approximately 3, 6 and 7 weeks (6. 9 and 10 weeks of age), groups of animals fed each diet were killed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The reduced expression of VEGF in metastatic colonies grown in EFAdeficient animals might reflect the reduced synthesis of PGE2 in these animals [25][26][27][28] -an observation in line with the finding that VEGF is reduced in animals fed n-3 PUFA-enriched diets [32,56], a dietary manipulation that reduces PGE2 synthesis [32].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…The reduced expression of VEGF in metastatic colonies grown in EFAdeficient animals might reflect the reduced synthesis of PGE2 in these animals [25][26][27][28] -an observation in line with the finding that VEGF is reduced in animals fed n-3 PUFA-enriched diets [32,56], a dietary manipulation that reduces PGE2 synthesis [32].…”
Section: Discussionsupporting
confidence: 53%
“…In conclusion, the data derived from the present study suggest that the reduced pulmonary colonization of B16-F10 cells represents the final step of a series of phenomena consisting in: decreased generation of prostaglandins due to EFA deficiency [25][26][27][28] -diminution of VEGF expression -reduced microvessel density -induction of apoptotic activity. This sequence, however, does not rule out the possibility that apoptosis might be primarily induced by the deprivation of an important nutritional factor, such as linoleic acid, in EFA-deficient animals.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This observation is consistent with a diminished renal PGE 2 excretion and vascular prostacyclin synthesis [6]. A primary factor in the control of prostaglandin synthesis in the renal papilla is the availability of the precursor [7]. In SHR there is a defect in the release of DGLA [8] and it was shown that dietary DGLA reverses hypertension induced in rats by diets rich in saturated fats, probably because in the microsomal fraction of the cell [10] by alternating sequences of desaturations and elongations.…”
Section: Introductionsupporting
confidence: 61%
“…It might also be illustrated by the fact that most patients after diagnosis have several years with very mild symptoms. It is also known that EFA deficiency may down-regulate the eicosanoid synthesis (46).…”
Section: Effects Of Increased Eicownoid Synthesismentioning
confidence: 99%